2022
DOI: 10.1007/s00277-021-04746-y
|View full text |Cite
|
Sign up to set email alerts
|

Management of herpesvirus reactivations in patients with solid tumours and hematologic malignancies: update of the Guidelines of the Infectious Diseases Working Party (AGIHO) of the German Society for Hematology and Medical Oncology (DGHO) on herpes simplex virus type 1, herpes simplex virus type 2, and varicella zoster virus

Abstract: Clinical reactivations of herpes simplex virus or varicella zoster virus occur frequently among patients with malignancies and manifest particularly as herpes simplex stomatitis in patients with acute leukaemia treated with intensive chemotherapy and as herpes zoster in patients with lymphoma or multiple myeloma. In recent years, knowledge on reactivation rates and clinical manifestations has increased for conventional chemotherapeutics as well as for many new antineoplastic agents. This guideline summarizes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 142 publications
0
16
0
1
Order By: Relevance
“…Antiviral prophylaxis, frequently used to prevent zoster reactivation in patients with cancer, provides another method of reducing the risk of severe COVID-19 (refs 210 , 211 ). The first trials aiming for COVID-19 prophylaxis clearly demonstrated that hydroxychloroquine is ineffective for this purpose 212 .…”
Section: Alternatives To Vaccinationmentioning
confidence: 99%
“…Antiviral prophylaxis, frequently used to prevent zoster reactivation in patients with cancer, provides another method of reducing the risk of severe COVID-19 (refs 210 , 211 ). The first trials aiming for COVID-19 prophylaxis clearly demonstrated that hydroxychloroquine is ineffective for this purpose 212 .…”
Section: Alternatives To Vaccinationmentioning
confidence: 99%
“…Multiple myeloma is with an incidence rate of 56/1000 person years known to be most at risk for HZ reactivation due to illness, but also treatment related immunocompromising conditions [ 3 ]. As most myeloma patients usually receive antineoplastic medication known to significantly elevate the risk for HZ, prophylactic application of acyclovir is standard of care [ 5 ], potentially triggering other preventive measures like vaccination. Nonetheless, of those patients being treated with these antineoplastic drugs, only 5% were vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…While incidence for HZ is 3.2 per 1000 person years in the overall population [ 4 ], this number rises to about 12 in patients with solid tumors and 31 in patients with hematological diseases [ 3 ]. Therefore, in hematological high-risk patients a HZ prophylaxis is recommended as it has been shown to provide a positive impact on mortality [ 5 ]. Specific antineoplastic or immunosuppressive medication further increases risk of VZV reactivation [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…2,38 Herpetic virus reactivation is common in the older frail population, a systematic review by the Multinational Association of Supportive Care in Cancer /International Society of Oral Oncology showed that aciclovir is effective in preventing oral herpetic viral disease in patients with hematologic malignancies 39 prophylactic aciclovir is relatively common in clinical practice and recent guidelines support this approach. 40 Baseline human immunodeficiency virus (HIV) and hepatitis B/C serology must be checked prior to starting chemotherapy and patients with past or active hepatitis B/C should receive appropriate prophylaxis and be discussed with a hepatologist/virologist.…”
Section: Antimicrobialsmentioning
confidence: 99%